Facile synthesis of gadolinium (III) chelates functionalized carbon quantum dots for fluorescence and magnetic resonance dual-modal bioimaging. (November 2015) - Shi, Yupeng; Pan, Yi; Zhong, Jian; Yang, Jun; Zheng, Junhui; Cheng, Jingliang; Song, Rong; Yi, Changqing
Abstract: Multi-modal imaging probes through synergistically combining two or more imaging modalities into single nanoparticle, offer possibilities to address multiple issues such as resolution, sensitivity, and tissue penetration. In this study, we report a facile strategy to synthesize a dual-modal fluorescence/magnetic resonance (MR) imaging nanoprobe with bright fluorescence and significantly improved relaxivity, where Gd 3+ ions are simply chelated onto the outer surface of the cyclic DTPA dianhydride (cDTPAA) functionalized carbon quantum dots (CQDs). Transmission electron microscopy, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and zeta potential measurements validated the successful preparation of CQD–DTPA–Gd. The surface conjugation of CQDs with cDTPAA and further Gd 3+ chelation does not perturb core optical properties of CQDs, and the thus prepared CQD–DTPA–Gd contain minimum Gd 3+ content (8.06%, w/w), while exhibiting significantly improved longitudinal relaxivity (56.72 mM −1 s −1 ). Excellent water solubility, good cell-membrane permeability and negligible cytotoxicity make CQD–DTPA–Gd an ideal dual-modal fluorescence/MR imaging probe, suggesting its potential and significance in practical bioimaging applications and medical translation in the future.